Mining Industry and US Government Cooperative Research: Lessons Learned and Benefits to the Mining Industry - Brian W. Stump; W Scott Philips; Robert Martin; David P. Anderson (International Society of Explosives Engineers, 1997)
Since 1994, various mines in the US have cooperated with research scientists at the Los Alamos and Lawrence Livermore National Laboratories to address issues related to verification of the Comprehensive Test Ban Treaty (CTBT). The .CTBT requires that no country may conduct any nuclear explosion in the future. While the CTBT is a significant step toward reducing the global nuclear danger, verifying compliance with the treaty requires that the monitoring system be able to detect, locate and identify much larger numbers of smaller amplitude seismic events than had been required previously. Large mining blasts conducted world-wide will be of sufficient amplitude to trigger the monitoring system at the lower threshold. It is therefore imperative that research into the range various blasting practices employed, the relationship of yield to seismic magnitude, and identification of anomalous blasting results be performed. This paper will describe a suite of experiments funded by the Department of Energy and conducted by the Los Alamos and Lawrence Livermore National Laboratories in cooperation with the US mining industry. Observations of cast blasting, underground long wall generated coal bumps, stoping, and explosively induced collapse of room and pillar panels will be presented. Results of these dual use experiments which are of interest to the mining community will be discussed. These include 1) variation of amplitude of seismic energy at various azimuths from cast blasts, 2) identification of the extent of back failure following explosive removal of pillars, and 3) the use of single fired shots for calibration of the monitoring system. The wealth of information and discovery described in this paper is a direct result of mutual cooperation between the US Government and the US Mining Industry.